2018
DOI: 10.3389/fneur.2018.00217
|View full text |Cite
|
Sign up to set email alerts
|

MOG-IgG-Associated Optic Neuritis, Encephalitis, and Myelitis: Lessons Learned From Neuromyelitis Optica Spectrum Disorder

Abstract: Antibodies against myelin oligodendrocyte glycoprotein (MOG-IgG) have been found in some cases diagnosed as seronegative neuromyelitis optica spectrum disorder (NMOSD). MOG-IgG allowed the identification of a subgroup with a clinical course distinct from that of NMOSD patients who are seropositive for aquaporin-4-IgG antibodies. MOG-IgG is associated with a wider clinical phenotype, not limited to NMOSD, with the majority of cases presenting with optic neuritis (ON), encephalitis with brain demyelinating lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
2
8

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 94 publications
4
117
2
8
Order By: Relevance
“…Multiple sclerosis (MS) remains the most common neuroinflammatory CNS disorder. Other “related” disorders such as acute disseminated encephalomyelitis and neuromyelitis optica (NMO) are now recognized to have distinct pathogenic mechanisms (Dos Passos et al, ). Animal models continue to be used as a foundation for defining mechanisms that may underlie development and course of MS.…”
Section: Comparison Of the Role Of Inflammation In Physiologic And Pamentioning
confidence: 99%
“…Multiple sclerosis (MS) remains the most common neuroinflammatory CNS disorder. Other “related” disorders such as acute disseminated encephalomyelitis and neuromyelitis optica (NMO) are now recognized to have distinct pathogenic mechanisms (Dos Passos et al, ). Animal models continue to be used as a foundation for defining mechanisms that may underlie development and course of MS.…”
Section: Comparison Of the Role Of Inflammation In Physiologic And Pamentioning
confidence: 99%
“…Thus, the recently described entity of MOG-IgG-associated optic neuritis, encephalitis, and myelitis (MONEM) may exist in this patient. 12 Long-term follow-up of the patient may further clarify the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of the events characterizing the syndrome (ADEM followed by ON) seems to depend on the typical distribution of ADS during childhood, with encephalopathic syndromes concerning younger children, and monofocal or multifocal nonencephalopathic events more typically affecting the older ones. 7,18 It has been demonstrated that MOG-abs are common in younger patients with encephalopa-thy and that MOG-abs syndromes frequently affect the optic nerves. 14 The data in the literature indicates that ADEM-ON represents a common evolution of MOG-abs seropositive patients who initially presented ADEM.…”
Section: Adem-onmentioning
confidence: 99%
“…Moreover, MOG-abs have been more recently detected in pediatric patients with different forms of monophasic or relapsing ADS, all grouped under the umbrella-term "MOG-spectrum disorder" (MOG-SD), including ADEM-ON as a distinct entity within this spectrum. [6][7][8] The goal of the current study is to review the literature on ADEM-ON, to analyze the demographic, clinical, laboratory, and radiological aspects of pediatric patients affected by this new subtype of ADS and to understand its clinical course and therapeutic features more completely.…”
Section: Introductionmentioning
confidence: 99%